Single stage repair of hypospadias with tabularized incised plate urethroplasty with partial degloving - Kegham, Hrair Haik; Shakir, Alaa Muneer; Ameen, Ali Abdulqader (International Surgery Journal, 2017)
Background: To evaluate tabularized incised plate (TIP) repair for hypospadias which is considered as the gold standard surgery by most surgeons at time being. The study discusses patients' selection, complications, and the outcome. Methods: Between April 2014 and April 2016, 42 boys, 2.5-10 years old (mean 5±1.6), underwent tabularized incised-plate (TIP) urethroplasty for primary hypospadias. The hypospadias defects included 16 distal (coronal or sub coronal), 15 distal penile and 11 mid shaft defects (5 of them were associated with mild chordae). With 3-6 months (mean 4±1.2) follow-up by history, examination and investigation. We considered the operations were successful in patients without any complications after 3 months from the surgery. Results: The success rate was 36 patients (86.7%), complications rate were 6 patients (14.3%). In early complications, we reported 3 patients had wound infection followed by wound dehiscence of glansplasty, and 2 patients had dehiscence of the glansplasty without infection, in late complications we reported one case of meatal stenosis with urethrocutaneous fistula, no cases of urethral stricture or diverticulae were reported. Conclusions: Single-stage repair of distal and midshaft penile hypospadias using tabularized incised-plate urethroplasty with partial degloving is a simple procedure; creates a normal appearing glandular meatus with functional neourethra in normal appearing circumcised penis, with high success and low complication rate in expert hands.